2002
DOI: 10.2337/diabetes.51.12.3532
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Tubular Epithelial Cells in Diabetic Nephropathy

Abstract: Previous studies have shown that renal function in type 2 diabetes correlates better with tubular changes than with glomerular pathology. Since advanced glycation end products (AGEs; AGE-albumin) and in particular carboxymethyllysine (CML) are known to play a central role in diabetic nephropathy, we studied the activation of nuclear factor B (NF-B) in tubular epithelial cells in vivo and in vitro by AGE-albumin and CML. Urine samples from healthy control subjects (n ‫؍‬ 50) and type 2 diabetic patients (n ‫؍‬ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
120
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(130 citation statements)
references
References 116 publications
9
120
1
Order By: Relevance
“…However, this is the first time that an increase in all three AGE subtypes has been demonstrated in ZDF rats, an increase that was suppressed simultaneously by drug intervention. In patients with diabetic nephropathy, urinary excretion of CML is reduced, and insufficient clearance may result in increased serum AGE concentrations as well as tissue accumulation of AGEs [26][27][28][29]. This is further supported by the fact that the AGE inhibitor aminoguanidine improved renal function in diabetic nephropathy, reduced tissue AGE deposits [30][31][32] and increased urinary excretion of dietary AGEs [33].…”
Section: Discussionmentioning
confidence: 91%
“…However, this is the first time that an increase in all three AGE subtypes has been demonstrated in ZDF rats, an increase that was suppressed simultaneously by drug intervention. In patients with diabetic nephropathy, urinary excretion of CML is reduced, and insufficient clearance may result in increased serum AGE concentrations as well as tissue accumulation of AGEs [26][27][28][29]. This is further supported by the fact that the AGE inhibitor aminoguanidine improved renal function in diabetic nephropathy, reduced tissue AGE deposits [30][31][32] and increased urinary excretion of dietary AGEs [33].…”
Section: Discussionmentioning
confidence: 91%
“…In this way, tubulointerstitial inflammation deteriorates renal function over time. Previous studies have shown that renal function in type 2 diabetes correlates better with tubular changes than with glomerular pathology (2,3). Further studies of tubulointerstitial disease in addition to glomerular injury in diabetes may provide additional insight into the pathogenesis of diabetic nephropathy and lead to the identification of targets for therapeutic intervention (17).…”
Section: Discussionmentioning
confidence: 99%
“…Where indicated, cells were pretreated for 1 h with 50 M PD98059, 30 min with 50 nM wortmannin, 2 h with 5 M PP1, or 30 min with 10 M U73122 or 5 M U73343 before the incubation with HGA. Where indicated, 50 g/ml of soluble RAGE (sRAGE) were added together with HGA for the appropriated times (32).…”
Section: Methodsmentioning
confidence: 99%